Pipeline rules of thumb handbook : quick and accurate solutions to your everyday pipeline problems - McAllister, E. W. (Elsevier, 2005)
Now in its sixth edition, Pipeline Rules of Thumb Handbook has been and continues to be the standard resource for any professional in the pipeline industry. A practical and convenient reference, it provides quick solutions to the everyday pipeline problems that the pipeline engineer, contractor, or designer faces. Pipeline Rules of Thumb Handbook assembles hundreds of shortcuts for pipeline construction, design, and engineering. Workable "how-to" methods, handy formulas, correlations, and curves all come together in this one convenient volume. * Save valuable time and effort using the thousands of illustrations, photographs, tables, calculations, and formulas available in an easy to use format. * Updated and revised with new material on project scoping, plastic pipe data, HDPE pipe data, fiberglass pipe, NEC tables, trenching, and much more. * A book you will use day to day guiding every step of pipeline design and maintenance